2006
DOI: 10.1007/s00192-006-0072-3
|View full text |Cite
|
Sign up to set email alerts
|

Changing prevalence and knowledge of urinary incontinence among Hong Kong Chinese women

Abstract: A territory-wide telephone survey was conducted in Hong Kong to assess the prevalence, knowledge, and treatment-seeking behaviour of Chinese women with urinary incontinence, using validated Chinese version of Urogenital Distress Inventory (UDI-6) and Incontinence Impact Questionnaire (IIQ-7). Women, 540, aged between 17 to 77 years were interviewed. Of the respondents, 40.8% reported stress urinary incontinence, 20.4% had urge incontinence and 15.9% had mixed incontinence. Among these, 16.0% reported quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 17 publications
3
29
2
Order By: Relevance
“…studies from Turkey observed that 12%-28% of affected women sought treatment [8][9][10], and other studies confirmed that only 1 in 4 women with incontinence sought medical help [4,16]. In most cases in the present study, medical attention was not sought because the nurses believed that urinary incontinence was a natural result of aging and childbirth-consistent with the majority of women in a previous study [4].…”
Section: I-qol and Subscalessupporting
confidence: 88%
See 1 more Smart Citation
“…studies from Turkey observed that 12%-28% of affected women sought treatment [8][9][10], and other studies confirmed that only 1 in 4 women with incontinence sought medical help [4,16]. In most cases in the present study, medical attention was not sought because the nurses believed that urinary incontinence was a natural result of aging and childbirth-consistent with the majority of women in a previous study [4].…”
Section: I-qol and Subscalessupporting
confidence: 88%
“…Van Geelen and Hunskaar [2] found that the prevalence of female urinary incontinence was between 10% and 50%. Although it is not a life-threatening condition, urinary incontinence has physical, mental, emotional, and economic dimensions [3], and despite it being one of the most common health problems experienced by women the majority postpone treatment because of embarrassment and self-neglect-considering it to be an unavoidable result of the aging process and childbirth [4]. Most women with urinary incontinence never seek professional help, and instead attempt to manage the condition on their own [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, only 4% of the women knew the physio therapists' role in this condition, with 13% know ing that there are exercises to treat this condition. This is in contrast with Wong et al (2006) who found that major ity of subjects in his study consulted a physiotherapist.…”
Section: Discussioncontrasting
confidence: 71%
“…Kim, McEwen, Sarma, Piette & Herman (2008) found that urinary incon tinence affected activities after delivery more frequently among women who were less educated and that higher levels of education and income were associated with low levels of incontinence. In a study done on Chinese women by Wong, Lau, Mak, Pang, Cheon and Yip (2006), the results showed that 78% of respondents did not know that urinary incontinence is a disease entity, but for those who sought treatment, physiotherapy was their first Not going to toilet 3 7.5…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies have reported low rates of help-seeking behaviors for UI [46,47]. The main reason given for these low rates was that UI was often viewed as a natural, inevitable, or normal consequence of aging or childbirth, rather than a medical condition that required help from healthcare professionals [48][49][50][51]. Correspondingly, women believed that UI was a long-term condition that needed self-management rather than treatment from others [52], or that there was no cure [53].…”
Section: Discussionmentioning
confidence: 93%